2015
DOI: 10.1111/tpj.12814
|View full text |Cite|
|
Sign up to set email alerts
|

A ‘golden’ SNP in CmOr governs the fruit flesh color of melon (Cucumis melo)

Abstract: Equal contribution. Accession numbers The sequences of melon CmOr (orange flesh haplotype and green or white flesh haplotype) were deposited in GenBank. Accession numbers are KM505046 and KM505047, respectively. SUMMARYThe flesh color of Cucumis melo (melon) is genetically determined, and can be white, light green or orange, with b-carotene being the predominant pigment. We associated carotenoid accumulation in melon fruit flesh with polymorphism within CmOr, a homolog of the cauliflower BoOr gene, and identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
170
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 44 publications
1
170
0
Order By: Relevance
“…The pleiotropic effects of BoOr and the multiple alternatively sliced transcripts of the naturally occurring BoOr active allele make it difficult to resolve the Or mechanism of action. We recently reported that b-carotene accumulation in melon fruit flesh is governed by a single SNP in CmOr, providing a precise biological tool with which to study OR function (Tzuri et al, 2015) and to utilize it in biotechnology (Yuan et al, 2015a). The identification of the novel low-b mutant provides an invaluable tool for further deciphering the Or gene mechanism of action in the regulation of carotenoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pleiotropic effects of BoOr and the multiple alternatively sliced transcripts of the naturally occurring BoOr active allele make it difficult to resolve the Or mechanism of action. We recently reported that b-carotene accumulation in melon fruit flesh is governed by a single SNP in CmOr, providing a precise biological tool with which to study OR function (Tzuri et al, 2015) and to utilize it in biotechnology (Yuan et al, 2015a). The identification of the novel low-b mutant provides an invaluable tool for further deciphering the Or gene mechanism of action in the regulation of carotenoid accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the golden SNP, which governs fruit flesh b-carotene levels across a wide spectrum of melon germplasm (Tzuri et al, 2015), was not associated with a reduction in PSY protein level. Green and orange 30-DAA melon fruits showed similar levels of PSY protein independently of the golden SNP genotype and accumulated a similar amount of phytoene 24 h after NF inhibition (Fig.…”
Section: Facilitation Of the Active Psy Enzymementioning
confidence: 99%
See 3 more Smart Citations